Implementation of an Integrated Cloud-Based Electronic Medical Record System at Community Health Center - Fu’ad, Raja Nasrul; Sugeng Riyadi; Deny Pratama; Ramadhan Wicaksono (Politeknik Ganesha Medan, 2025)
Klambir Lima is a village located in Hamparan Perak District, Deli Serdang Regency, North Sumatra Province. It is a small village with a dense population but has only one government community health center (puskesmas). This results in suboptimal patient services. Furthermore, there is no existing application for recording patient data or medical records that could assist in patient data management. Patient medical records are a crucial feature in healthcare services. They are useful for recording or storing a patient's health or illness history, which enables accurate treatment or medication tailored to the patient's needs. Therefore, the Klambir Lima Health Center requires an electronic medical records application based on Cloud Computing. Data will be stored in cloud storage, aiming to minimize damage or loss of data, which is a vital asset. In this research, the author developed the application using the R&D (Research and Development) method. The role and utility of the research were well established to ensure better implementation of the application. The research objective is to create a system capable of recording electronic-based medical records via cloud computing media. This will enable the Klambir Lima Health Center to improve its healthcare services for both BPJS (national health insurance) and non-BPJS patients